Quick-fixing: Near-rationality in consumption and savings behavior - Peter Andre; Joel P. Flynn; George Nikolakoudis; Karthik A. Sastry (Leibniz Institute for Financial Research SAFE, 2024)
The near-rationality hypothesis holds that even very small costs of optimization may lead people to act suboptimally. We embed this idea in a standard model of consumption-savings decisions: households pursue simple quick-fix consumption policies unless they pay a cost to optimize. We design a novel survey to explore this theory. The survey elicits households' hypothetical consumption responses to a large number of unanticipated income shocks, allowing us to estimate household-level consumption policies. Consistent with the theory, 68% of households follow one of four simple quick-fix consumption rules that either fully consume or fully save out of small shocks before abruptly switching to similar consumption policies for large shocks. Households' quick-fixing types account for 49% of the variance in MPCs across households, despite not being predictable by other demographic and economic information. Quantitatively, an incomplete-markets model calibrated to our survey findings generates more than three times as much size-dependence in the aggregate consumption response to government transfer shocks as the nested rational model. This large difference in behavior arises while households experience consumption-equivalent welfare costs of near-rationality of at most 65 per quarter.
Keywords: E21; E71; 330